Analysis of the needs for RADEC-based social studies teaching materials - Sri Rohartati; Bunyamin Maftuh; Wahyu Sopandi; Rachmat Setiawan; Hendy Satria Nugraha; Putri Fatimatuz Zuhro (Global Econedu, 2026)
This study aimed to analyze the need for developing RADEC-based Social Studies teaching materials to enhance environmental literacy among elementary school students in the Sarimukti Landfill area, West Bandung Regency. A descriptive qualitative approach was employed involving teachers and fifth-grade students from elementary schools located near the Sarimukti Landfill. Data were collected through questionnaires, observations, and interviews and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings revealed a strong need for contextual teaching materials that support reading activities, analytical questioning, collaborative discussions, concept explanation, and project creation. Students demonstrated positive responses to the RADEC learning stages and showed high interest in environmental learning, although their understanding of environmental issues remained limited. RADEC-based Social Studies teaching materials are needed to provide meaningful learning experiences and strengthen students’ environmental literacy through contextual environmental issues surrounding the Sarimukti Landfill.